Val av tidpunkt för markberedning vid naturlig föryngring under skärm av Pinus sylvestris i Svealand - Lennartsson, Andreas (SLU/Dept. of Forest Products, 2005)
This thesis is built on a field study that was carried out in two seed-tree stands near by Götbrunna in Uppland, Sweden. The aim was to examine if scarification carried out in spring time could generate a more dense seedling establishment when using natural generation, than scarification carried out in autumn. It was also investigated whether there were differences in mortality the first season between the two plot-types. Plots were established block-wise with 50 blocks (pairs) on each site. The spring scarification was made with a hoe during 22-23 of April. The shelterwood densities were 120-130 stems ha-1 and the seedfalls were registered by five seed-traps in each stand.